1992
DOI: 10.1080/09064709209410123
|View full text |Cite
|
Sign up to set email alerts
|

Heat—Moisture Treatment of Rapeseed Meal: Effect on Digestibility of the Diet, Voluntary Grass Silage Intake and Growth Rate of Ayrshire Bulls

Abstract: Animal Production, SF-31600 Jokioinen, Finland). Heat-moisture treatment of rapeseed meal: effect on digestibility of the diet, voluntary grass silage intake and growth rate of Ayrshire bulls. Accepted November 13, 1991. Aeta Agric. Scand., Sect. A, Animal Sci. 42: 157-166, 1992.Forty-eight Finnish Ayrshire bulls of average live weight 106 kg at the start and 432 kg at the end of the experiment were fed grass silage ad libition and restricted amounts of concentrates consisting of barley alone (treatment A), or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 23 publications
2
12
2
Order By: Relevance
“…In the study of Olsson (1987) BWG was numerically greater (60 g/day) in cattle fed SBM compared with those fed high glucosinolate RSM, but there was no difference between the control diet without supplementary protein and SBM diet. The results of the study by Aronen and Vanhatalo (1992) suggest that the effects of RSM on BWG can be more related to the concentration of glucosinolates than to protein degradability.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the study of Olsson (1987) BWG was numerically greater (60 g/day) in cattle fed SBM compared with those fed high glucosinolate RSM, but there was no difference between the control diet without supplementary protein and SBM diet. The results of the study by Aronen and Vanhatalo (1992) suggest that the effects of RSM on BWG can be more related to the concentration of glucosinolates than to protein degradability.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that the inclusion of rapeseed meal (RSM) in the barley grain-based concentrate with grass silage (Huuskonen et al, 2007 and or whole-crop barley silage (Huuskonen, 2013) -based diets did not affect performance of growing dairy bulls. However, inclusions of RSM in the grass silage plus barley-based diet had positive effects on the performance of young bulls and bull calves in some feeding experiments (Aronen and Vanhatalo, 1992;, and including RUP increased the BW gain (BWG) of young steers offered grass silage plus low levels of concentrate (Moloney, 1991;Rouzbehan et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In some earlier studies on growing dairy bulls with separate feeding the RSM supplementation increased the intake of hay (Aronen 1990) or grass silage (Aronen 1990, Aronen and Vanhatalo 1992a but, for example, Huhtanen et al (1985Huhtanen et al ( , 1989 Differences between the diets were compared using an a priori test (Dunnett's test) so that comparison of the diets was based on the C diet. Contrasts: (1 = C vs. RSM), (2 = C vs. WDS),…”
Section: Discussion Feed Intake and Diet Digestibilitymentioning
confidence: 99%
“…In some feeding experiments (Joki-Tokola 1991, Aronen et al 1992, Aronen andVanhatalo 1992a), partial replacement of cereal grains by protein feeds had a positive effect on live weight gain (LWG), while in others the effect was non-existent (Huhtanen et al 1989, Aronen 1990, Huuskonen et al 2007a). The improved LWG may have been related either to an increased uptake of amino acids or to improved digestibility of the diet and thereby increased feed intake (Aronen and Vanhatalo 1992b).…”
Section: Introductionmentioning
confidence: 99%
“…Huuskonen et al (2007 reported that RSM did not affect animal performance of finishing dairy bulls (from 6.0 to 18.0 months of age), and concluded that there is no reason to use protein supplement for finishing dairy bulls when they are fed with good quality grass silage and barley-based concentrate. However, inclusion of RSM in the diet was found to have a positive effect on the performance of young bulls and bull calves in some feeding experiments Vanhatalo 1992). The growth and feed efficiency over the whole growth period, including preweaning, postweaning and finishing periods, are critical also from the economic viewpoint.…”
Section: Introductionmentioning
confidence: 99%